Coverage of foreign labor in the Icelandic media – does the media really reflect trends? - Kristjánsson, Klemenz Hrafn; Sigurðardóttir, Margrét Sigrún; Jóhannsdóttir, Valgerður (School of Social Sciences, 2023)
The ratio of foreign nationals in the Icelandic labour market has grown quite a lot in the last few years, rising from 4% in 2006 to 13% in 2017. Foreigners have been met with some prejudice in the Icelandic labour market and there are indications that media coverage does not reflect their high numbers in Iceland. In this article we look at the media coverage of foreign nationals in the Icelandic labour market in three Icelandic media outlets from 2006 to 2017. The coverage is not extensive but it does seem to follow the ratio of foreign nationals in the labour market. The coverage was greatest in the beginning of the research period, when the political party Frjálslyndi flokkurinn put the danger of free flow of labour on its agenda. The media coverage of foreign labour is mostly positive, although in some cases foreign labour has been pitted against the elderly and disabled. The ratio of media coverage of foreign labour in the total labour market coverage is, however, higher than the ratio of foreign workers in the labour market. Erlendum ríkisborgurum á íslenskum vinnumarkaði hefur fjölgað mjög undanfarin ár Hlutfall erlends vinnuafls fór úr tæplega 4% árið 2006 í rúmlega 13% árið 2017 Erlendir ríkisborgarar hafa orðið fyrir ákveðnum fordómum á íslenskum vinnumarkaði og vísbendingar eru um að umfjöllun fjölmiðla endurspegli ekki hlutfall erlendra ríkisborgara í íslensku samfélagi Í þessari grein skoðum við umfang og eðli umfjöllunar um erlent vinnuafl í þremur íslenskum fréttamiðlum frá árinu 2006 til ársins 2017 Umfjöllun um erlent vinnuafl virðist að ákveðnu marki fylgja hlutfalli erlends vinnuafls á vinnumarkaði innan tímabilsins Mest var umfjöllunin í upphafi rannsóknartímabilsins, en þann topp má rekja til þess að Frjálslyndi flokkurinn gerði áhættuna sem gæti stafað af innflutningi erlends vinnuafls að kosningamáli fyrir þingkosningarnar 2007 Umfjöllun um erlent vinnuafl var þó almennt frekar jákvæð en neikvæð, þótt erlendu vinnuafli sé í einhverjum tilfellum stillt upp sem andstöðu við öryrkja og ...